Impact of specialized oral nutritional supplement on clinical, nutritional, and functional outcomes: A randomized, placebo-controlled trial in community-dwelling older adults at risk of malnutrition - Chew, Samuel Teong Huang (CHURCHILL LIVINGSTONE, 2023)
10.1016/j.clnu.2020.10.015